Incidental Finding of Persistent Hydatidiform Mole in an Adolescent on Depo-Provera - Olukayode Akinlaja; Rebecca McKendrick; Zineb Mashak; May Nokkaew (Hindawi Limited, 2016)
Molar pregnancies represent an uncommon yet important obstetric problem with potentially fatal outcomes. Patients typically present with signs and symptoms of early pregnancy, and physicians most often suspect nonmolar pregnancy complications initially; however a hydatidiform mole should be included in the differential diagnosis of a woman with a positive pregnancy test and abnormal vaginal bleeding irrespective of the use of contraception. Our case is that of an adolescent female on Depo-Provera injectable contraceptive with increased vaginal bleeding, abdominal pain, nausea, and vomiting who was incidentally found to be pregnant and subsequently diagnosed with a molar pregnancy despite persistent denial of having initiated sexual intercourse. Though gestational trophoblastic disease is uncommon with an incidence of about 1-2 cases per 1,000 pregnancies, a clinician has to display a high index of suspicion when dealing with patients at extremes of age in order to avoid potentially life-threatening outcomes.